Coating fluid for forming composite clay film, composite clay film and its manufacturing method, and laminate having composite clay film and its manufacturing method

JP7632819B2Active Publication Date: 2025-02-19KUNIMINE IND CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021008510
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-22
Publication Date
2025-02-19
Estimated Expiration
2041-01-22

AI Technical Summary

Benefits of technology

【0008】 本発明の複合粘土膜及び積層体は、優れた耐水性を示し、かつ、高度なガスバリア性をも示す。また本発明の複合粘土膜及び積層体の製造方法によれば、優れた耐水性を示し、かつ、高度なガスバリア性をも示す複合粘土膜ないし積層体を得ることができる。また本発明の複合粘土膜形成用塗工液は、優れた耐水性を示し、かつ、高度なガスバリア性をも示す複合粘土膜ないし積層体の形成に好適に用いることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007632819000001
    Figure 0007632819000001
  • Figure 0007632819000002
    Figure 0007632819000002
Patent Text Reader

Abstract

To provide a functional film that is primarily composed of clay mineral but shows excellent water resistance and also has high-level gas barrier properties and a method for producing the same, and a coating liquid suitable for forming the functional film.SOLUTION: The present invention discloses a composite clay film comprising a composite of clay mineral and butene diol vinyl alcohol copolymers, with the content of the clay mineral being 55-85 mass% and the content of butene diol vinyl alcohol copolymers being 15-45 mass% and a method for producing the same. There are also provided a laminate having the composite clay film and a method for producing the same, and a coating liquid for forming a composite clay film, which is suitable for forming the composite clay film and the laminate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coating liquid for forming a composite clay film, a composite clay film and a method for producing the same, and a laminate having a composite clay film and a method for producing the same. [Background technology]

[0002] Films whose main component is organic polymers (organic polymer films) are used as packaging and sealing materials for food, medicines, chemicals, electronic device parts, etc. Organic polymer films have excellent flexibility and processability, and depending on the type, they exhibit various functions such as water resistance and gas barrier properties. In order to improve the functionality of organic polymer films, composite films in which different types of organic polymer films are bonded together, organic polymer films on which metals or metal oxides are vapor-deposited, etc. have been developed and are widely used. However, the production of these films increases the equipment costs, and the produced films are relatively expensive. In terms of gas barrier properties, the molecular motion of the polymer chains in organic polymer films becomes more intense at high temperatures. Therefore, gas molecules tend to pass through the gaps between the polymer chains at high temperatures. In other words, the gas barrier properties of organic polymer films tend to decrease significantly at high temperatures. Therefore, it is difficult for organic polymer films to fully maintain and develop barrier properties, especially against gases with small molecular sizes such as hydrogen and helium, even at high temperatures.

[0003] Clay films mainly composed of clay minerals have been proposed as functional film materials other than organic polymers. Clay minerals have a structure in which plate-like crystals (crystal layers) that are approximately 1 nm thick and spread two-dimensionally from 20 to 2000 nm in width are layered. If clay minerals are mixed into a medium such as water, the clay mineral crystals naturally peel off, making it relatively easy to disperse the clay minerals in the medium. Then, when this dispersion liquid (slurry) is applied to a substrate and dried, a clay film with layered crystal layers due to its self-laminating properties can be obtained. Gas molecules cannot pass through the clay crystals, and the clay film has excellent gas barrier properties. However, clay films are easily compatible with water, so there are limitations to improving their water resistance. A technique for compounding clay minerals with organic polymers has been proposed as a technique for improving the water resistance of clay films. For example, Patent Document 1 describes a clay film formed using a clay slurry containing a layered silicate compound, a carboxyl group-containing resin, a crosslinking agent having a functional group reactive to a carboxyl group, and water. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2016-169135 A Summary of the Invention [Problem to be solved by the invention]

[0005] As a result of the inventors' investigations, it has been found that in the technology described in Patent Document 1, the crosslinking reaction occurs during the drying process, so that the film is formed without sufficient removal of the solvent, and as a result, it is difficult to sufficiently improve the barrier properties against small molecular gases such as hydrogen and helium at high temperatures. In other words, a clay film that has both high water resistance and high gas barrier properties has not been realized. The present invention aims to provide a functional film that exhibits excellent water resistance and also has high gas barrier properties while being mainly composed of a clay mineral, and a method for producing the same, and also aims to provide a coating liquid suitable for forming the functional film. [Means for solving the problem]

[0006] The present inventors have conducted various studies in view of the above problems. As a result, they have found that a composite clay film, which is composed mainly of clay minerals and is composited with butenediol-vinyl alcohol copolymer, has excellent water resistance and also excellent barrier properties against hydrogen gas and the like at high temperatures. Based on these findings, the present invention has been completed through further studies.

[0007] The above-mentioned object of the present invention has been achieved by the following means. <1> A coating liquid for forming a composite clay film, comprising water, a clay mineral, and a butenediol-vinyl alcohol copolymer, the clay mineral content in the solid matter being 55-85% by mass, and the butenediol-vinyl alcohol copolymer content being 15-45% by mass. <2> The clay mineral includes at least one of montmorillonite, mica, vermiculite, beidellite, saponite, hectorite, stevensite, magadiite, ilealite, and kanemite; <1> 2. The coating liquid for forming a composite clay film according to claim 1 . <3> The clay mineral includes montmorillonite. <1> or <2> 2. The coating liquid for forming a composite clay film according to claim 1 . <4> A composite clay film comprising a clay mineral and a butenediol-vinyl alcohol copolymer, the clay mineral content being 55 to 90 mass % and the butenediol-vinyl alcohol copolymer content being 10 to 45 mass %. <5> When the thickness of the composite clay film is 2 μm, the hydrogen permeability is 30 cm at 150 °C. 3 / m 2 / day(24 hours) / atm or less, <4> The composite clay film according to claim 1. <6> A supporting substrate and a film formed on the supporting substrate. <4> or <5> A laminate having the composite clay film according to claim 1. <7> <1> ~ <3> The method includes applying the composite clay film-forming coating liquid according to any one of the above onto a supporting substrate to form a coating film, and drying the coating film to obtain a composite clay film on the supporting substrate. <4> or <5> A method for producing the composite clay film described in claim 1. <8> <1> ~ <3> The coating liquid for forming a composite clay film according to any one of the above is applied onto a supporting substrate to form a coating film, and the coating film is dried. <6> A method for producing the laminate described in claim 1. <9> After drying the coating film, the dried coating film is subjected to a heat treatment of 130°C or higher. <7> or <8> The manufacturing method described in Effect of the Invention

[0008] The composite clay film and laminate of the present invention exhibit excellent water resistance and also exhibit high gas barrier properties. In addition, according to the manufacturing method of the composite clay film and laminate of the present invention, a composite clay film or laminate exhibiting excellent water resistance and also exhibiting high gas barrier properties can be obtained. In addition, the coating liquid for forming a composite clay film of the present invention can be suitably used for forming a composite clay film or laminate exhibiting excellent water resistance and also exhibiting high gas barrier properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] A preferred embodiment of the present invention will now be described.

[0010] [Coating fluid] The coating fluid for forming a composite clay film of the present invention (hereinafter also referred to as "the coating fluid of the present invention") contains water, a clay mineral, and a butenediol vinyl alcohol copolymer (hereinafter also referred to as "BVOH"). In the solid content of the coating fluid of the present invention (in the components excluding the medium (solvent)), the clay mineral content is 55 to 85 mass%, and the BVOH content in the solid content is 15 to 45 mass%. The coating fluid of the present invention is usually a dispersion in which clay is dispersed in water or an aqueous medium (a mixture of water and a water-soluble organic solvent) in which BVOH is dissolved. When clay minerals are mixed with a medium such as water, the crystal layers separate and are dispersed in the medium. When BVOH is added, the BVOH dissolves in the medium, and a uniform mixture (slurry, coating liquid) of the clay mineral and BVOH can be obtained. When this slurry is applied to a support substrate and the coating is dried, a composite clay film is obtained in which the clay mineral and BVOH are composited (integrated) at the nano level. In the present invention, the "composite" of the clay mineral and BVOH refers to a composite film obtained through the above-mentioned slurry coating to drying processes. Each component constituting the coating solution of the present invention will be described below.

[0011] <Clay minerals> The coating liquid of the present invention contains a specific amount of clay mineral. The clay mineral is composed of a layered silicate compound, and the gas barrier property is not easily deteriorated even at high temperatures. In addition, the crystal layer of the clay mineral basically does not allow gas to pass through, and has excellent barrier properties against hydrogen gas and helium gas, which have small molecular sizes. The clay mineral used in the present invention may be natural or synthetic. The clay mineral used in the present invention preferably contains at least one of montmorillonite, mica, vermiculite, beidellite, saponite, hectorite, stevensite, magadiite, ilerite, and kanemite. The clay mineral preferably contains at least one of these in an amount of 80% by mass or more, more preferably 90% by mass or more. The clay mineral used in the present invention is more preferably at least one of montmorillonite, mica, vermiculite, beidellite, saponite, hectorite, stevensite, magadiite, ilerite, and kanemite. Among them, the clay mineral used in the present invention preferably contains at least one of montmorillonite, mica, beidellite, saponite, and hectorite, and more preferably contains montmorillonite. The clay mineral used in the present invention is preferably at least one of montmorillonite, mica, beidellite, saponite, and hectorite, and particularly preferably contains montmorillonite.

[0012] From the viewpoint of dispersibility in a medium such as water and applicability of a coating liquid, the clay mineral is preferably one or more selected from Na-type clay, Li-type clay, K-type clay, and NH4-type clay, more preferably Na-type clay or Li-type clay. In addition, for example, in consideration of further improving the water resistance of a clay film formed using a slurry, one or more polyvalent cation clays selected from Mg-type clay, Ca-type clay, Al-type clay, and Cu-type clay can also be used. Here, the Na type, Li type, K type, NH4 type, Mg type, Ca type, Al type, and Cu type clays are classified into two types: Na type, Li type, K type, NH4 type, Mg type, Ca type, Al type, and Cu type clays, and the Na type clays are classified into two types: Na type, Li type, K type, NH4 type, Mg type, Ca type, Al type, and Cu type clays.+ , Li + , K + , NH4 + , Mg 2+ , Ca 2+ , Al 3+ , and Cu 2+ This refers to clay in which the amount of (unit: meq / 100g) is 70% or more. In this specification, the amount of leached cations in clay is calculated by leaching the interlayer cations of clay using 100 mL of 1 M ammonium acetate aqueous solution (1 M sulfuric acid for Al-type clay, 10 mass % potassium chloride aqueous solution for NH4-type clay) per 0.5 g of clay for 4 hours, and measuring the concentrations of various cations in the obtained solution using ICP emission spectrometry, atomic absorption spectrometry, an ammonia electrode, etc.

[0013] In the solid content of the coating liquid of the present invention, the content of the clay is 55 to 85 mass%, preferably 57 to 83 mass%, more preferably 58 to 82 mass%, and even more preferably 59 to 81 mass%. The content is also preferably 65 mass% or more, and also preferably 70 mass% or more.

[0014] The clay minerals used in the present invention can be commercially available, for example, Kunipia-F, which is a refined natural bentonite mainly composed of Na-montmorillonite, Kunipia-M, which is a refined natural bentonite mainly composed of Li-montmorillonite, Sumecton-SA as a synthetic saponite, Sumecton-ST as a synthetic stevensite, and Sumecton-SWN as a synthetic hectorite (all manufactured by Kunimine Kogyo Co., Ltd.).

[0015] <Butenediol vinyl alcohol copolymer (BVOH)> The coating liquid of the present invention contains a specific amount of BVOH. By containing a specific amount of BVOH, the gas barrier property of the clay film can be fully expressed while effectively increasing the water resistance of the clay film. That is, since BVOH is water-soluble, it can form a uniform mixture with the clay mineral at the nano level, and in the obtained film, it functions as a binder that fills the voids of the clay particles without any gaps, and a composite clay film in which the clay mineral and BVOH are composited (integrated) at the nano level can be formed. The reason why the composite clay film formed in this way exhibits high gas barrier property is not clear, but one of the reasons is thought to be the formation of strong hydrogen bonds between the clay crystals and BVOH.

[0016] The BVOH used in the present invention can be obtained by hydrolyzing a copolymer obtained by the reaction of 3,4-diacetoxy-1-butene and vinyl acetate. The BVOH used in the present invention may be a random copolymer or a block copolymer. The copolymerization ratio of 3,4-diacetoxy-1-butene and vinyl acetate used as raw monomers of BVOH is not particularly limited. For example, it can be [3,4-diacetoxy-1-butene]:[vinyl acetate]=1:99 to 99:1 (molar ratio), and it is also preferable to set [3,4-diacetoxy-1-butene]:[vinyl acetate]=10:90 to 90:10 (molar ratio), and it is also preferable to set [3,4-diacetoxy-1-butene]:[vinyl acetate]=20:80 to 80:20 (molar ratio). The polymerization degree of BVOH is not particularly limited. For example, it can be 100 to 10,000, preferably 200 to 5,000, and more preferably 250 to 3,000. The smaller the polymerization degree of BVOH, the lower the viscosity of the dispersion liquid, which is preferable from the viewpoint of handling. The saponification degree of BVOH is preferably 70 mol % or more, more preferably 80 mol % or more, and even more preferably 90 mol % or more. The higher the saponification degree, the higher the water resistance of the resulting composite clay film tends to be.

[0017] BVOH can be obtained from the market, and a preferred example is G-polymer (manufactured by Mitsubishi Chemical Corporation, saponification degree 95.0 mol % or more). BVOH can also be obtained by addition polymerization of monomers by a conventional method.

[0018] In the solid content of the coating liquid of the present invention, the content of the butenediol-vinyl alcohol copolymer is 15 to 45 mass%, preferably 17 to 43 mass%, more preferably 18 to 42 mass%, and even more preferably 19 to 41 mass%. The content is also preferably 35 mass% or less, and also preferably 30 mass% or less.

[0019] <Other ingredients> The coating fluid of the present invention may contain a silane coupling agent, a crosslinking agent, an organic polymer other than BVOH, silica, a surfactant, inorganic nanoparticles, etc., within the range that does not impair the effects of the present invention. The total content of these components is usually 10 mass % or less of the solid content of the coating fluid.

[0020] [Preparation of coating liquid] The coating fluid of the present invention can be prepared, for example, by mixing a clay mineral and, if necessary, other components with water or an aqueous medium to prepare a clay dispersion, and then mixing this clay dispersion with an aqueous BVOH solution. The aqueous solvent includes water and a water-soluble organic solvent. The aqueous medium is preferably 50% by mass or more of water, more preferably 70% by mass or more of water, even more preferably 80% by mass or more of water, particularly preferably 90% by mass or more of water, and may be 100% by mass of water (not including organic solvent). There is no particular limitation on the water-soluble organic solvent, and it is appropriately selected according to the purpose. For example, alcohols such as ethanol, isopropanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,3-butylene glycol, pentamethylene glycol, hexylene glycol, hexylene glycol, 1,3-butanediol, 1,4-butanediol, glycerin, diglycerin, and polyglycerin can be mentioned, and one or more of these can be used. The content of the clay mineral in the clay dispersion can be, for example, about 1 to 30 mass %, and is also preferably about 5 to 20 mass %. The solubility of BVOH in water can be increased by heating it to about 50 to 90° C. The content of BVOH in the aqueous BVOH solution can be about 1 to 10% by mass, and is also preferably 3 to 7% by mass.

[0021] The preferred contents of the clay and BVOH in the solid content of the coating solution of the present invention are as described above. From the viewpoint of coatability, the solid content concentration of the coating solution of the present invention is preferably 2 to 10 mass %, more preferably 3 to 7 mass %.

[0022] The method for mixing the clay dispersion and the BVOH aqueous solution is not particularly limited, and for example, they can be mixed using a common stirrer or mixer such as a bladed stirrer, a planetary mixer, a universal mixer, or a homomixer.

[0023] [Composite clay film] The composite clay film of the present invention is formed by compositely combining a clay mineral and a butenediol-vinyl alcohol copolymer as described above, and has a clay mineral content of 55 to 90 mass % and a butenediol-vinyl alcohol copolymer content of 10 to 45 mass %. The composite clay film of the present invention has high gas barrier properties. When the composite clay film is formed to a thickness of 2 μm, the hydrogen permeability is 30 cm at 150° C. 3 / m 2 / day / atm or less, preferably 20cm 3 / m 2 / day / atm or less, and more preferably 10cm 3 / m 2 / day / atm or less, and more preferably 5cm 3 / m 2 The hydrogen permeability of the gas barrier film of the present invention is measured by the method described in the examples below.

[0024] [Method of manufacturing composite clay film] The composite clay film of the present invention can be obtained on a supporting substrate by applying the coating liquid of the present invention onto a supporting substrate to form a coating film, and then drying the coating film. The shape of the support substrate is not particularly limited, and may be a plate, sheet, or film, or may be a three-dimensional shape. Examples of the film include polyethylene terephthalate film and polypropylene film. Examples of the material on the support substrate include resins such as phenol resin, epoxy resin, and polycarbonate resin. In order to improve the adhesion between the composite clay film of the present invention and the supporting substrate, the supporting substrate may be subjected to frame treatment, corona treatment, or silane coupling agent treatment, or the supporting substrate may be surface-treated using an aqueous resin solution, emulsion, or a commercially available anchor coating agent.

[0025] The method for applying the coating liquid of the present invention is not particularly limited, and examples thereof include a spray method, a spin coating method, a dip method, a roll coating method, a blade coating method, a doctor roll method, a doctor blade method, a curtain coating method, a slit coating method, a screen printing method, an inkjet method, and a dispense method.

[0026] The drying temperature for the coating film is not particularly limited and can be, for example, 70 to 120° C. The drying time can be any time that the coating film can be sufficiently dried, and can be, for example, 1 minute to 24 hours, preferably 15 minutes to 12 hours, and preferably 20 minutes to 3 hours. In addition, after drying the coating film, it can be subjected to a heat treatment at, for example, 130°C or higher (preferably 140°C or higher, more preferably 150°C or higher) within the range of the heat resistance temperature of the supporting substrate. The heat treatment time is preferably 1 minute to 24 hours, more preferably 15 minutes to 12 hours, and more preferably 20 minutes to 3 hours. Although a composite clay film exhibiting sufficiently high water resistance and gas barrier properties can be obtained without this heat treatment, the solvent can be completely removed by heat treatment, and a more densified composite clay film with higher water resistance and higher gas barrier properties can be obtained. That is, it is also a preferred embodiment that the composite clay film of the present invention is a product heat-treated at 130°C or higher. The degree of densification by heat treatment can be understood to some extent by measuring the density of the composite clay film and shifting the value of the 001 peak of X-ray diffraction to a high angle, but it is difficult to specifically and accurately specify the structure of the composite clay film, and in the present invention, the state of the clay composite film may be specified by its heat treatment temperature as described above. The heat treatment temperature is usually 200°C or lower.

[0027] [Laminate and its manufacturing method] The laminate of the present invention has the above-mentioned supporting substrate and the composite clay film of the present invention formed on the supporting substrate. The laminate of the present invention may be a two-layer structure of a supporting substrate and a composite clay film, and may further have another layer on the surface of the supporting substrate or the composite clay film. For example, a primer layer such as a silane coupling agent layer or a resin layer may be present between the supporting substrate and the composite clay film. In addition, a coating layer formed of a resin or the like may be present on the surface of the composite clay film opposite to the supporting substrate side or the surface of the supporting substrate opposite to the composite clay film side. The preferred forms of the supporting substrate and the composite clay film thereon constituting the laminate of the present invention, and the preferred embodiment of the method for forming the composite clay film on the supporting substrate are as described above. EXAMPLES

[0028] The present invention will now be described in more detail with reference to the following examples. However, the present invention is not limited to these examples except as defined in the present invention.

[0029] <Preparation of coating liquid> - Preparation of Coating Liquid 1 - 10 parts by mass of Li-type montmorillonite (product name: Kunipia-M, manufactured by Kunimine Industries Co., Ltd.) was mixed with 90 parts by mass of distilled water by stirring in a universal mixer (manufactured by Aiko Co., Ltd.) to obtain a paste containing 10% by mass of Li-type montmorillonite. Separately, 90 parts by mass of distilled water was mixed with 10 parts by mass of BVOH (G-polymer manufactured by Mitsubishi Chemical Corporation), and distilled water at 60 to 80° C. was further added to dissolve the BVOH, thereby obtaining an aqueous BVOH solution in which BVOH was dissolved at a concentration of 5% by mass. The obtained paste, an aqueous BVOH solution, and distilled water were mixed, and the mixture was stirred and mixed with a dispersing blade of a Three-One Motor (manufactured by AS ONE Corporation) so that the solid content was 5 mass%, the content of Li-type montmorillonite in the solid content was 80 mass%, and the content of BVOH in the solid content was 20 mass%, thereby obtaining Coating Solution 1.

[0030] - Preparation of Coating Liquid 2 - Coating Liquid 2 was obtained in the same manner as in Coating Liquid 1, except that Na-montmorillonite (Kunipia-F, manufactured by Kunimine Kogyo Co., Ltd.) was used instead of Li-montmorillonite.

[0031] - Preparation of Coating Liquid 3 - Coating Liquid 3 was obtained in the same manner as in Coating Liquid 1, except that the paste, the BVOH aqueous solution, and distilled water were stirred and mixed so that the content of Li-montmorillonite in the solid content of the obtained coating liquid was 60 mass% and the content of BVOH in the solid content was 40 mass%. The solid content of Coating Liquid 3 was 5 mass%.

[0032] -Preparation of Comparative Coating Solution 1- The 5 mass % BVOH aqueous solution used in the preparation of Coating Solution 1 was used as Comparative Coating Solution 1.

[0033] - Preparation of Comparative Coating Solution 2 - 95 parts by mass of distilled water and 5 parts by mass of Li-montmorillonite (product name: Kunipia-M, manufactured by Kunimine Industries Co., Ltd.) were mixed and stirred in a universal mixer (manufactured by Aiko Co., Ltd.) to obtain a comparative coating solution 2 containing 5% by mass of Li-montmorillonite.

[0034] - Preparation of Comparative Coating Solution 3 - 95 parts by mass of distilled water and 5 parts by mass of Na-montmorillonite (product name: Kunipia-F, manufactured by Kunimine Kogyo Co., Ltd.) were mixed and stirred in a universal mixer (manufactured by Aiko Co., Ltd.) to obtain a comparative coating solution 3 containing 5% by mass of Na-montmorillonite.

[0035] - Preparation of Comparative Coating Solution 4 - Comparative Coating Liquid 4 was obtained in the same manner as in Coating Liquid 1, except that in the preparation of Coating Liquid 1, the paste, the BVOH aqueous solution, and distilled water were stirred and mixed so that the content of Li-montmorillonite in the solid content of the obtained coating liquid was 20 mass% and the content of BVOH in the solid content was 80 mass%. The solid content of Comparative Coating Liquid 4 was 5 mass%.

[0036] - Preparation of Comparative Coating Solution 5 - Comparative Coating Liquid 5 was obtained in the same manner as in Coating Liquid 1, except that in the preparation of Coating Liquid 1, the paste, the BVOH aqueous solution, and distilled water were stirred and mixed so that the content of Li-montmorillonite in the solid content of the obtained coating liquid was 40 mass% and the content of BVOH in the solid content was 60 mass%. The solid content of Comparative Coating Liquid 5 was 5 mass%.

[0037] - Preparation of Comparative Coating Solution 6 - Comparative Coating Liquid 6 was obtained in the same manner as in the preparation of Coating Liquid 1, except that the paste, the BVOH aqueous solution, and distilled water were stirred and mixed so that the content of Li-montmorillonite in the solid content of the obtained coating liquid was 90 mass% and the content of BVOH in the solid content was 10 mass%. The solid content of Comparative Coating Liquid 6 was 5 mass%.

[0038] - Preparation of Comparative Coating Solution 7 - Comparative Coating Liquid 7 was prepared in the same manner as Coating Liquid 1, except that a 5 mass% water-soluble nylon (product name: AQ Polymer, manufactured by Toray Industries, Inc.) aqueous solution was used instead of the 5 mass% BVOH aqueous solution in the preparation of Coating Liquid 1. The solid content of Comparative Coating Liquid 7 was 5 mass%.

[0039] - Preparation of Comparative Coating Solution 8 - In preparation of Coating Liquid 1, an aqueous solution containing equal amounts of ethylene-acrylic acid copolymer (product name: ZAIKXEN A, manufactured by Sumitomo Seika Chemicals) and polycarbodiimide (Carbodilite V-02, manufactured by Nisshinbo Chemical Co., Ltd.) was used instead of the 5 mass% BVOH aqueous solution to prepare Comparative Coating Liquid 8, in which the contents of ethylene-acrylic acid copolymer and polycarbodiimide in the solid content were both 15 mass% (clay mineral concentration in the solid content was 70 mass%). The solid content of Comparative Coating Liquid 8 was 5 mass%.

[0040] [Examples 1 to 3, Comparative Examples 1 to 6] Each of Coating Liquids 1 to 3 and Comparative Coating Liquids 1 to 6 was applied onto a PET film using a casting knife, and the film was treated at 80° C. for 2 hours and then at 150° C. for 1 hour. In this manner, a laminate having a composite clay film, a clay film, or a BVOH film on the PET film was obtained. Each laminate was cut into a 5 cm square, immersed in distilled water, and left to stand at room temperature for 24 hours. The state of the film (film on the PET film) after immersion for 24 hours was observed, and the water resistance was evaluated according to the following criteria. Coating Liquids 1 to 3 correspond to Examples 1 to 3, respectively, and Comparative Coating Liquids 1 to 6 correspond to Comparative Examples 1 to 6, respectively. The results are shown in Table 1.

[0041] -Evaluation criteria for water resistance- A: No change in shape, no tackiness B: No change in shape, tacky C: Disintegrated or dissolved in water

[0042] [Table 1]

[0043] The composite clay films formed from comparative coating liquids 2 and 3, which do not contain BVOH, swelled immediately after immersion in water and collapsed. In addition, the results of the composite clay film formed from comparative coating liquid 6 showed that even if BVOH was contained, if the amount was less than that specified in the present invention, the film was easily mixed with water and showed tackiness (adhesiveness) when immersed in water. In addition, the composite clay films formed from comparative coating liquids 4 and 5, which have a BVOH content in the solid content greater than that specified in the present invention, also collapsed or dissolved after immersion in water, or the film surface was mixed with water and showed tackiness. In addition, when a film was formed using comparative coating liquid 1, which is an aqueous BVOH solution, the film surface was easily mixed with water and showed tackiness. On the other hand, the composite clay films formed from Coating Liquids 1 to 3 maintained their shape for a long time even when immersed in water, did not show tackiness, and exhibited excellent water resistance.

[0044] [Example 4] After washing the support substrate of phenolic resin (thickness about 1.8 mm) with alcohol, a solution of N-2-(aminoethyl)-3-aminopropyltrimethoxysilane (KBM-603, manufactured by Shin-Etsu Chemical Co., Ltd.) dissolved in isopropyl alcohol at a concentration of 1% by mass as a silane coupling agent was applied to the washed surface and dried, and the support substrate surface was treated with the silane coupling agent. Then, the coating liquid 1 was spray-coated on the silane coupling agent-treated surface so that the thickness after drying was 2 μm, and dried at 80 ° C. for 30 minutes. Next, the temperature was raised to 160 ° C. over 30 minutes, and the heat treatment was performed at 160 ° C. for 30 minutes. In this way, a laminate in which a composite clay film was formed on the support substrate was obtained. The hydrogen gas permeability of this laminate, the high temperature water resistance of the composite clay film, and the weather resistance of the composite clay film were evaluated by the method shown below. The results are shown in Table 2.

[0045] [Example 5] A laminate was obtained in the same manner as in Example 4, except that BVOH (1 mass % aqueous solution) was used instead of the silane coupling agent, and was subjected to each evaluation test.

[0046] [Comparative Example 7] A laminate was obtained in the same manner as in Example 4, except that Comparative Coating Liquid 7 was used instead of Coating Liquid 1 in Example 4 and the heat treatment temperature after drying was set to 150°C, and then subjected to each evaluation test.

[0047] [Comparative Example 8] A laminate was obtained in the same manner as in Example 4, except that Comparative Coating Fluid 8 was used instead of Coating Fluid 1 in Example 4, and was subjected to each evaluation test.

[0048] [Comparative Example 9] The phenolic resin supporting substrate itself was subjected to each evaluation test.

[0049] <Hydrogen gas permeability measurement> The hydrogen gas permeability of each test piece was measured at 150° C. using a differential pressure gas permeability measuring device (device names: GTR-30XAD2 and G2700, manufactured by GTR Tech Co., Ltd. and Yanaco Technical Science Co., Ltd., respectively).

[0050] Each laminate (Comparative Example 9 was phenolic resin substrate only, same below) was immersed in distilled water in a beaker, and the distilled water was boiled for 1 hour, and the high temperature water resistance of the laminate was evaluated according to the following criteria. -Evaluation criteria for high temperature and water resistance- A: No change in shape, no tackiness B: No change in shape, tacky C: Disintegrated or dissolved in water

[0051] Each laminate was treated at 121° C. for 1 hour using an autoclave (Science Autoclave NCC-1701B, AS ONE Corporation), and the weather resistance (high temperature and high humidity resistance) of the test pieces was evaluated according to the following criteria. -Weather resistance evaluation criteria- A: The clay composite film did not peel off from the supporting substrate and maintained its shape before autoclaving. C: The clay composite film was peeled off from the supporting substrate and the film collapsed.

[0052] [Table 2]

[0053] The hydrogen gas permeability of the phenolic resin support substrate is very high, and the phenolic resin support substrate exhibits almost no hydrogen gas barrier properties (Comparative Example 9). Therefore, the hydrogen gas permeability of each of the laminates in Examples 4 and 5 and Comparative Examples 7 and 8 can be regarded as the hydrogen gas permeability of each composite clay film provided in each laminate. As shown in Table 2 above, the laminates of Comparative Examples 7 and 8, in which a resin other than BVOH was used as the resin to be composited with the clay mineral, were inferior in hydrogen gas barrier properties, high-temperature water resistance, and weather resistance. In contrast, the laminates of Examples 4 and 5 having the composite clay film of the present invention exhibited excellent gas barrier properties even at high temperatures, and were also excellent in high-temperature water resistance and weather resistance.

Claims

1. A coating solution for forming a composite clay film, comprising water, a clay mineral, and a butenediol-vinyl alcohol copolymer, The clay mineral is selected from Na-montmorillonite and Li-montmorillonite; The content of the clay mineral in the solid content of the composite clay film-forming coating liquid is 55 to 85 mass %, and the content of the butenediol-vinyl alcohol copolymer is 15 to 45 mass %, The composite clay film obtained by drying the coating of the coating liquid for forming a composite clay film does not increase in tackiness even when immersed in water at room temperature for 24 hours.

2. A coating solution for forming a composite clay film, comprising water, a clay mineral, and a butenediol-vinyl alcohol copolymer, The clay mineral is selected from Na-montmorillonite and Li-montmorillonite; The content of the clay mineral in the solid content of the composite clay film-forming coating liquid is 55 to 85 mass %, and the content of the butenediol-vinyl alcohol copolymer is 15 to 45 mass %, In the butenediol-vinyl alcohol copolymer, the content ratio of a component derived from 3,4-diacetoxy-1-butene to a component derived from vinyl acetate is [3,4-diacetoxy-1-butene]:[vinyl acetate]=20:80 to 80:20 (molar ratio); The composite clay film-forming coating liquid, wherein the butenediol-vinyl alcohol copolymer has a degree of saponification of 80 mol % or more.

3. A composite clay film formed by combining a clay mineral and a butenediol-vinyl alcohol copolymer, The clay mineral is selected from Na-montmorillonite and Li-montmorillonite; The content of the clay mineral is 55 to 85% by mass, and the content of the butenediol-vinyl alcohol copolymer is 15 to 45% by mass, A composite clay film whose tackiness does not increase even when immersed in water at room temperature for 24 hours.

4. A composite clay film formed by combining a clay mineral and a butenediol-vinyl alcohol copolymer, The clay mineral is selected from Na-montmorillonite and Li-montmorillonite; The content of the clay mineral is 55 to 85% by mass, and the content of the butenediol-vinyl alcohol copolymer is 15 to 45% by mass, In the butenediol-vinyl alcohol copolymer, the content ratio of a component derived from 3,4-diacetoxy-1-butene to a component derived from vinyl acetate is [3,4-diacetoxy-1-butene]:[vinyl acetate]=20:80 to 80:20 (molar ratio); The butenediol-vinyl alcohol copolymer has a degree of saponification of 80 mol % or more.

5. When the thickness of the composite clay film is 2 μm, the hydrogen permeability is 30 cm at 150° C. 3 / m 2 5. The composite clay film according to claim 3, wherein the surface tension is 100 nm / day / atm or less.

6. A laminate having a supporting substrate and the composite clay film according to any one of claims 3 to 5 formed on the supporting substrate.

7. The method for producing the composite clay film according to any one of claims 3 to 5, comprising applying the composite clay film-forming coating liquid according to claim 1 or 2 onto a supporting substrate to form a coating film, and drying the coating film to obtain a composite clay film on the supporting substrate.

8. A method for producing the laminate according to claim 6, comprising applying the composite clay film-forming coating liquid according to claim 1 or 2 onto a supporting substrate to form a coating film, and drying the coating film.

9. 9. The method according to claim 7 or 8, wherein after drying the coating film, the dried coating film is subjected to a heat treatment at 130° C. or higher.

Citation Information

Patent Citations

  • Gas barrier film

    JP2001009983A

  • Resin composition, aqueous coating liquid using the same, and multilayered structural body

    JP2007161795A

  • Clay slurry and clay film

    JP2016169135A

  • Wavelength conversion film

    JP2018120058A